Enhancing Soybean Physiology and Productivity Through Foliar Application of Soluble Monoammonium Phosphate - Vitor Alves Rodrigues; Luiz Gustavo Moretti; Israel Alves Filho; Marcela Pacola; Josiane Viveiros; Lucas Moraes Jacomassi; Sirlene Lopes Oliveira; Amine Jamal; Tatiani Mayara Galeriani; Murilo de Campos; José Roberto Portugal; João William Bossolani; et al. (Agronomy)
Phosphorus (P) is essential for crop growth, but its complex behavior in tropical soils necessitates alternative management strategies, such as foliar supplementation. Foliar-applied nutrients act as biostimulants, enhancing stress tolerance and plant productivity. This study assessed the physiological responses of soybean to foliar application of soluble monoammonium phosphate (MAP; at a rate of 5 kg ha−1 each application) at different phenological stages (two during vegetative stages V4 and V6 and two during reproductive stages R1 and R3 or all four stages) across two growing seasons in tropical field conditions. Key parameters analyzed included leaf nutrient content, photosynthetic pigments, Rubisco activity, carbohydrate content, gas exchange (photosynthetic rate, stomatal conductance, transpiration, water use efficiency, and carboxylation efficiency), oxidative stress markers, and productivity indicators (100-grain weight and grain yield). MAP application improved all parameters, particularly at R1 and R3. Total chlorophyll increased by 29.2% at R1 and 30.0% when applied at all four stages, while the net photosynthetic rate rose by 15.8% and 18.4%, respectively. Water use efficiency improved by 20.0% at R1 and all four stages, while oxidative stress indicators, such as H2O2 levels, decreased. Rubisco activity increased most at R3 (46.0%) and all four stages (59.9%). Grain yield was highest with MAP spread at all four stages (12.3% increase), though a single application at R1 still boosted yield by 7.4%, compared to the control treatment.